Catechol‐Based Molecular Memory Film for Redox Linked Bioelectronics. (19th July 2020) - Wu, Si; Kim, Eunkyoung; Chen, Chen‐yu; Li, Jinyang; VanArsdale, Eric; Grieco, Christopher; Kohler, Bern; Bentley, William E.; Shi, Xiaowen; Payne, Gregory F.
Abstract: Redox is emerging as an alternative modality for bio‐device communication. In contrast to the more familiar ionic electrical modality: (i) redox involves the flow of electrons through oxidation–reduction reactions; (ii) the aqueous medium is an "insulator" to this electron flow since free electrons do not normally exist in water; and (iii) redox states are intrinsically digital (oxidized and reduced). By exploiting these unique features, a catechol‐based molecular memory film is reported. This memory is fabricated by electrochemically grafting catechol to a chitosan–agarose polysaccharide network to generate a redox‐active but non‐conducting matrix. The redox state of the grafted catechol moieties serves as the 2‐state memory. It is shown that these redox states: can be repeatedly switched by diffusible mediators (electron shuttles); can be easily read electrically or optically; are stable for at least 2 h in the absence of energy; are sensitive to biologically relevant oxidizing and reducing contexts; and can be switched enzymatically. This catechol‐based molecular memory film is a simple circuit element for redox linked bioelectronics. Abstract : A catechol‐based molecular memory‐film that is easy to fabricate, employs a simple 2‐state redox mechanism, and is conveniently read by orthogonal optical and electrical measurements is reported. The redox memory states are stable for hours and can be repeatedly switched. Importantly, this memory can be switched by both electrochemical and biological mechanisms, which provides a communication bridge for redox‐linked bioelectronics.